PENINGKATAN OKSIGEN TERLARUT (AERASI) DENGAN MENGGUNAKAN PIPA – U - Dewi, Ratni; Sari, Ratna (Jurnal Sains dan Teknologi Reaksi, 2003)
Water is an essential substance in the human daily life. One of the criteria of healthy water is represented by its dissolved oxygen content. In this research, the water used came from the drilled well and after being treated hopefully the dissolved oxygen in the water will increase. Dissolved oxygen contained in water originated from the air and from the photosynthesis process of water plants. The capability of oxygen to dissolve in water are effected by temperature, barometric air pressure or high and the mineral content in the water. This research‘s goal is to anylize dissolved oxygen content in the water after being treated to several different variables such as pipe length, air flow velocity and water flow velocity. From the interaction of these variable we will find which variable is most significant. The outcome of the the research show that air flow velocity has an influence on the dissolved oxygen content in which the higher the air flow velocity, dissolved oxygen in the water is increase. Water flow velocity has a significant influence on dissolved oxygen content where the lower the water flow velocity will increase the dissolved oxygen in the water.Key Word : Dissolved Oxygen